ANALYTICAL FOUNDATIONS OF ELECTROTECHNOLOGICAL TREATMENT METHODS FOR AGRICULTURAL CROP SEEDS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article presents an analysis of devices that enhance the efficiency of electrotechnological treatment of agricultural crop seeds.